Significado da formação docente e os sentidos atribuídos em pesquisas de intervenção: um estudo das teses e dissertações defendidas na região Centro-Oeste - Gimenes, Oliria Mendes (2012)
Teachers education has been the object of interest of several intervention researches being carried out at Masters Levels and doctoral degrees. Those researches have proposed formation processes from different approaches (concepts and practices) in teachers training. These studies, in theory, rely on these theoretical perspectives (which have a social definite meaning) and convert them into practical training (which express the meanings attributed by the researchers approaching teachers education). Under this premise, this study aimed to understand the social significance of academic researches on teachers education and the personal sense given in the context of theses and dissertations that have developed intervention research in Post-Graduate Education Programs in the Midwest, from 1999 to 2008. We opted for a qualitative research methodology through a dialectical approach in data analysis, being adopted two methodological procedures: one for the collection and data processing and the other for analysis. At first we used the Wordsmith Tools software, from Corpus Linguistics as a technological resource that was used for computer categorization. In the second, clusters were taken as units of meaning, relating to the prospects of training, and analyzed from the perspective of the Historic-Cultural Theory, specifically, the category meaning and sense. According to the systematized data, the analysis has portrayed the approaches and objectifications of the formative processes present in the studies analyzed, from the analysis of clusters relating the prospects for teachers education, the authors, and the practical training proposed by the researches authors. The survey collected data that allowed us to observe that the (non)coincidence between what is culturally approached by researchers who are teachers trainers (meaning) and the training practices proposed by them in the polls (sense) reveals the conception of the researcher and his training process, once he has approached meaning and sense, indicating in these cases, differences between the socially constructed and what is personally assigned. Thus, we conclude that during the process of signification the researcher has been exposed to situations that have made him approach sometimes wrongly or contrary to the meaning set in, raising the same way senses that do not correspond to that meaning, a condition favorable for alienation of both the researcher-trainer and the teacher in the training process. Thus, teaching learning triggered by teacher s training processes is therefore tied to the quality of tools and signs that mediate the formation processes experienced. It depends on the content, means and methods proposed. Ultimately mediational processes are defining the ownership of the social meaning and the attribution of meaning constituted in the training processes and teaching practice, which can humanize the teacher or trainer, or alienate them.